PEMANFAATAN PROBIOTIK UNTUK MENINGKATKAN KUALITAS PAKAN TERNAK SAPI PADA KELOMPOK TERNAK DI TASIKMALAYA - Agustian, Dita; Nuryadin, Egi; Aisyah, Iis (Jurnal Abdi Insani, 2024)
The need for cheap and quality feed is one of the main challenges faced by every cattle breeder, both on farms with breeding and fattening concepts. Quality animal feed is always synonymous with expensive prices, making it difficult for cattle breeders to obtain, the majority of whom are small to medium scale breeders. One way to produce cheap and high-quality feed is to make fermented feed from forage grass or rice straw. This program aims to help breeders in producing cheap and high-quality feed from available ingredients and even from materials that are considered waste. The implementation of the program is carried out by socializing and simulating the manufacture of fermented feed directly by breeders accompanied by a community service implementation team. The results show that the knowledge and skills of farmers in producing fermented feed have increased significantly, the animal's palatability to the feed has increased, and the amount of manure has decreased. It is hoped that this training can increase the competency of breeders in producing cheap and high-quality feed, so that they can increase profits by reducing operational costs, making time efficient, as well as utilizing and reducing waste that can pollute the environment.